A critical analysis of the Mises stress criterion used in frequency domain fatigue life prediction - Adam Niesłony (Fracture and Structural Integrity)
Multiaxial fatigue failure criteria are formulated in time and frequency domain. The number of frequency domain criteria is rather small and the most popular one is the equivalent von Mises stress criterion. This criterion was elaborated by Preumont and Piefort on the basis of well-known von Mises stress concept, first proposed by Huber in 1907, and well accepted by the scientific community and engineers. It is important to know, that the criterion was developed to determine the yield stress and material effort under static load. Therefore the direct use of equivalent von Mises stress criterion for fatigue life prediction can lead to some incorrectness of theoretical and practical nature. In the present study four aspects were discussed: influence of the value of fatigue strength of tension and torsion, lack of parallelism of the SN curves, abnormal behaviour of the criterion under biaxial tensioncompression and influence of phase shift between particular stress state components. Information contained in this article will help to prevent improper use of this criterion and contributes to its better understanding